Characteristics and quality assessment of GRADE practice guidelines on maternal-fetal care - Andelys De la Rosa (Medwave)
The study aimed to assess the quality and applicability of current maternal-fetal health clinical practice guidelines that countries can adopt or adapt. A systematic search was conducted in the International Database of GRADE Guidelines (BIGG) for practice guidelines developed with the GRADE system (Grades of Recommendation, Assessment, Development, and Evaluation) and related to maternal-fetal care. The selected guidelines were evaluated with the AGREE-REX (Appraisal of Guidelines REsearch and Evaluation-Recommendations Excellence) tool to assess clinical applicability (domain-1), values and preferences (domain-2) and applicability (domain-3). The variables were presented descriptively, and a statistical analysis was performed on the domains according to institution and country of origin. Of 1,212 clinical practice guidelines, 72 met the inclusion criteria. According to the type of collaborating organization, the World Health Organization predominated with 58.3%, versus specialized medical societies. Domain 1, “Clinical applicability,” was the best rated by the reviewers (68.5%) compared to domain 2, “Values and preferences” (60%). According to the type of institution that developed the clinical practice guideline, a significant difference was demonstrated in domains 1 (p= 0.000), 2 (p= 0.006) and 3 (p= 0.000). Only domains 1 (p= 0.000) and 3 (p= 0.018) were statistically significant based on country of origin. This study emphasizes the importance of improving the quality of maternal-fetal clinical practice guidelines developed by organizations and governmental institutions and the need to strengthen the institutionalization of the use of evidence to develop, adapt and implement practice guidelines in countries such as the United Kingdom, Canada, Spain, Colombia, the United States, among others.